Acoustic scattering from a bubbly-liquid-filled compliant cylinder - Wilson, PS; Roy, RA; Carey, WM (Acoustical Society of America, 2001)
Acoustic scattering from a bubbly cylinder has been studied experimentally to determine the utility of effective medium scattering theory for a well defined shape. A bubble filled latex tube was submerged horizontally in a large tank, and its backscatter strength was measured for frequencies ranging from 5–20 kHz. Results show that the effective medium theory continues to be valid at higher frequencies, provided the scatterer’s shape is known.